Remaja Perempuan Sebagai Korban Kekerasan Fisik Dan Mental Dalam Toxic Relationship : Perlindungan Hukum Pidana Dan Perlindungan Sosial - Izmail Yusuf Khatami; Levina; Rosalinda Paulina Benyamin; Sofie Indriana Salsabila (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The phenomenon of toxic relationships has become increasingly prevalent among adolescents, particularly young women who are vulnerable to both physical and psychological abuse. This study aims to explore the forms of violence experienced by victims, examine their level of legal awareness, and analyze the existing mechanisms of criminal and social protection available to them. Using questionnaires and interviews with 50 respondents aged 15–22 years. The results show that 78% of respondents experienced psychological violence such as excessive control, verbal humiliation, and emotional manipulation (gaslighting), while 26% reported physical violence including pushing and slapping. Only 34% of respondents were aware of legal protections for victims, yet 98% had never reported their experiences due to fear, shame, or lack of knowledge about reporting mechanisms. Social support was mostly obtained from peers (60%) rather than family (20%), with some family members even blaming the victims. These findings reveal that the willingness of victims to report remains very low, hindered by psychological and social barriers as well as limited legal understanding. Therefore, strengthening legal education, psychological support, and protective policies is essential to ensure that young women receive adequate safety, empowerment, and justice from both their communities and the state.